The Level of Readiness of Refrigeration and Air Conditioning Program Students in Facing Online Learning during COVID-19 Pandemic - Wan Ab Aziz, Wan Ahmad Faisal; Wan Muda, Wan Hanim Nadrah; Chidozie, Chinedu Caleb; Ismail, Nurtasnim (Online Journal for TVET Practitioners, 2021)
The spread of Covid-19 has affected the education sector in Malaysia. The closure of higher educational institutions due to the Covid-19 pandemic has affected the structure of learning and teaching, from physical learning and teaching methods in institutions to fully online learning and teaching. The main objective of this study was to study the level of readiness of Refrigeration and Air Conditioning Program Refrigeration and Air Conditioning Program Program students in facing online learning during the Covid-19 pandemic. This study uses a quantitative approach with descriptive research designs and survey methods. the instrument used in this study was a questionnaire that has been distributed to the respondents for their feedback. The population involved in this study is 111 students in Faculty of Technical and Vocational Education, Universiti Tun Hussein Onn Malaysia (UTHM. The data obtained was analyzed using IBM Statistic SPSS software version 23. Results of data analysis indicated that the mean score for the attitude of the participating students is 3.36, whereas the mean scores for the aspects of the motivation, knowledge of existing technology, and internet access were recorded as 3.66, 3.86, and 3.77 respectively. In conclusion, the level of readiness of students of Refrigeration and Air Conditioning Program in facing online learning is at a moderate level.